Nuclear physics midterm plan at LNS - Agodi, Clementina; Cappuzzello, F.; Cardella, G.; Cirrone, G. A. P.; De Filippo, E.; Di Pietro, A.; Gargano, A.; La Cognata, M.; Mascali, D.; Milluzzo, G.; Nania, R.; Petringa, G.; et al. (The European physical journal. Plus, 2023)
The next years will see the completion of several new facilities at Istituto Nazionale di Fisica Nucleare - Laboratori Nazionali del Sud (LNS) opening up new possibilities in the fields of nuclear structure, nuclear dynamics, nuclear astrophysics and applications. These include a new line for high-intensity cyclotron beams, a new facility for in-flight production of radioactive ion beams, the PANDORA plasma trap for multidisciplinary studies and a high-power laser for basic science and applied physics. The nuclear physics community has organized a workshop to discuss the new physics opportunities that will be possible in the middle term (5-7 years) by employing state-of-the-art detection systems. A detailed discussion of the outcome from the workshop is presented in this report.